DYNAMICS OF CHANGES IN PROINFLAMMATORY CYTOKINES IN PATIENTS WITH FRACTURES OF THE LONG BONES OF THE LOWER LIMB WITH MULTIPLE INJURIES (ResearchJet Journal of Analysis and Inventions, 2023)
The objects of clinical study were 48 patients with polytrauma admitted to the department of emergency traumatology of the Multidisciplinary Clinic of the Tashkent Medical Academy.